Role of strigolactones in adventitious rooting of Arabidopsis thaliana callus in vitro - Claassens, Adrianus Petrus (Stellenbosch : Stellenbosch University, 2025)
Claassens, Adrianus Petrus. 2024. Role of strigolactones in adventitious rooting of Arabidopsis thaliana callus in vitro. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131623